2017
DOI: 10.1128/jvi.00463-17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inner Nuclear Membrane Proteins SUN1/UNC-84A and SUN2/UNC-84B on the Early Steps of HIV-1 Infection

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection of dividing and nondividing cells involves regulatory interactions with the nuclear pore complex (NPC), followed by translocation to the nucleus and preferential integration into genomic areas in proximity to the inner nuclear membrane (INM). To identify host proteins that may contribute to these processes, we performed an overexpression screen of known membrane-associated NE proteins. We found that the integral transmembrane proteins SUN1/UNC84A and SUN2/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 97 publications
5
31
0
Order By: Relevance
“…Given that SUN1 and SUN2 share many functional similarities, we investigated whether SUN1 regulates HIV-1 infection. During the preparation of this paper, Schaller et al reported that SUN1 overexpression blocks HIV-1 infection in a CA-dependent manner (25). Our results reported here confirm their results.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Given that SUN1 and SUN2 share many functional similarities, we investigated whether SUN1 regulates HIV-1 infection. During the preparation of this paper, Schaller et al reported that SUN1 overexpression blocks HIV-1 infection in a CA-dependent manner (25). Our results reported here confirm their results.…”
supporting
confidence: 90%
“…5). During the course of our work, Schaller et al (25) reported that SUN1 overexpression inhibits the infection of HIV-1 by reducing the accumulation of the 2-LTR DNA in a CA-dependent manner. Our findings reported here are consistent with theirs.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Detailed methods are provided in the online version of this paper and include the following: cells (Merck Millipore) as previously described (Schaller et al, 2017). Briefly, CANC expression was induced with 1 mM of isopropyl b-D-thiogalactopyranoside (IPTG) for 6 h at 30 C. Cells were collected by centrifugation and lysed by sonication.…”
Section: Star+methodsmentioning
confidence: 99%